Transient out-of-SOA robustness of SiC power MOSFETs - Castellazzi, Alberto; Fayyaz, Asad; Romano, Gianpaolo; Riccio, Michele; Irace, Andrea; Urresti-Ibanez, Jesus; Wright, Nick (2017)
Beyond their main function of high-frequency switches in modulated power converters, solid-state power devices are required in many application domains to also ensure robustness against a number of overload operational conditions. This paper considers the specific case of 1200 V SiC power MOSFETs and analyses their performance under three main transient regimes at the edge of and out of their Safe Operating Area: unclamped inductive switching led avalanche breakdown; short-circuit; operation as current limiting and regulating devices. The results presented highlight both inherent major strengths of SiC over Si and areas for improvement by tailored device design. The paper aims to contribute useful indications for technology development in future device generations to better match widespread and varied application requirements.